2001
DOI: 10.1038/sj.mp.4000869
|View full text |Cite
|
Sign up to set email alerts
|

A missense mutation in a novel gene encoding a putative cation channel is associated with catatonic schizophrenia in a large pedigree

Abstract: Schizophrenia is a common and etiologically heterogeneous disorder. Although inheritance of schizophrenic syndromes is complex with genetic and environmental factors contributing to the clinical phenotype, periodic catatonia, a familial subtype of catatonic schizophrenia, appears to be transmitted in an autosomal dominant manner. We report here that a Leu309Met mutation in WKL1, a positional candidate gene on chromosome 22q13.33 encoding a putative non-selective cation channel expressed exclusively in brain, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
1

Year Published

2002
2002
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 19 publications
4
64
1
Order By: Relevance
“…We sequenced exon 11 and its intron/exon boundaries in 174 UK schizophrenics, including cases of 22 cases of catatonic schizophrenia, and did not identify any individual that contained the mutation described by Meyer et al 1 However, we did observe a novel insertion/deletion polymorphism (with a predicted amino acid insertion of AGEVSGLWGGG 350 -351), one-missense substitution (N344S) and two synonymous substitutions in exon 11 (1174C4T and 1192T4C). In addition, we also identified a nucleotide substitution in intron 11 (IVS11+27A4G (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We sequenced exon 11 and its intron/exon boundaries in 174 UK schizophrenics, including cases of 22 cases of catatonic schizophrenia, and did not identify any individual that contained the mutation described by Meyer et al 1 However, we did observe a novel insertion/deletion polymorphism (with a predicted amino acid insertion of AGEVSGLWGGG 350 -351), one-missense substitution (N344S) and two synonymous substitutions in exon 11 (1174C4T and 1192T4C). In addition, we also identified a nucleotide substitution in intron 11 (IVS11+27A4G (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…1 The protein is predicted to have eight transmembrane domains and one of these occurs in exon 11. 1,2 Structural prediction analyses of the mutation found in the large pedigree with catatonic schizophrenia indicates that the presence of this missense mutation is likely to result in conformational changes of the mutant protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34 However, both the same group and others have more recently rejected this hypothesis based on more extensive analyses of a number of catatonic families. [35][36][37] Interestingly, a recent study of a Southern Indian population reported evidence of association between MLC1 and both SZ and BPD.…”
Section: Discussionmentioning
confidence: 99%